Findings about the early medieval fortification of the Mikulčice – Valy acropolis - Marian Mazuch (Slavia Antiqua, 2007)
The author evaluates the available information about the fortifications of the Mikulčice acropolis, the main area of the Early Medieval agglomeration. He gives a new perspective on the structure and dating of the fortification based on analyzing the documentation of all conducted excavations. Great Moravian rampart is composed of a stone face wall, clay-wood core strengthened by grates and a stone substructure ringed by stake palisades, in front of, and in some places partially under, the face wall. The substructure’s role was most likely to bear the face wall’s weight and to strengthen the artificial slope under it against water erosion by the nearby river. The defensive wall was built in a relatively short time as a singular structure, probably in the last third of the 9th century.